Collaborative studies on in vitro digestibility of dietary proteins based on the INFOGEST Quant protocol: toward international standardization - Lotti Egger; Ana Blanco-Doval; Cédric Brügger; Raquel Sousa; Lychou Abbühl; Marta Santos Hernández; Beatriz Miralles; Cristina Gómez-Marin; Adam Macierzanka; Patrycja Szumała; Ilona E. Kłosowska-Chomiczewska; Ana Isabel Mulet-Cabero; et al. (Food Research International, 2026)

Breathing lung-on-chip: a versatile tool for assessing respiratory toxicity across multiple therapeutic modalities - Linnea Johansson; Giulia Raggi; James Cartwright; Johnny Lindqvist; Laurène Froment; Patrik Andersson; Catherine Betts; Jorrit J. Hornberg; Nina Hobi; Anna Ollerstam; Paul Fitzpatrick (Archives of Toxicology, 2026)

Direct and indirect ecosystem responses to vehicle compaction of soft sediments - C.Haleh Mawson; Athena Webster; James Fitzpatrick; Jennifer L. Ruesink (Marine Environmental Research, 2025)

Evaluating uncertainties with sample-collection method and source selection in sediment fingerprinting: an example from a Great Lakes tributary - Tanja N. Williamson; James D. Blount; Heidi M. Broerman; Faith A. Fitzpatrick; Isaac J. Mevis; Dayle J. Hoefling; Shannon M. Pace; Matthew J. Komiskey; Rebecca M. Kreiling (Journal of Soils and Sediments, 2025)
Purpose Identifying suspended-sediment (SS) sources, seasonal variability, and phosphorus (P) transported with SS is critical information for basin managers, although there may be concerns about comparability between flow-integrated SS samples used for sediment fingerprinting and discrete samples used for concentrations and loads in basins where SS is mostly silt + clay and(or) one land-use predominates. Objectives were to determine if (1) sample-collection method and (2) source consideration influenced apportionment of the largest SS source. Methods Concurrent-replicate, SS samples were collected during 2022 from the East River, Wisconsin using an automated sampler, commonly used for water-quality sampling, and passive samplers, frequently used for SS fingerprinting. Samples were evaluated for differences in physical and chemical characteristics that may affect source apportionment. Considered sources included three upland land-use (cropland, forest, and roads), two in-channel (streambank and streambed sediment), and one that connects uplands to the stream channel (gullies). Source apportionment used established methods in the SedSAT tool. Source scenarios included land-use + streambank (4src), 4src + gully, 4src + streambed, and 4src + gully + streambed (6src). Results There were no statistically significant differences in median grain size, organic carbon, or sediment-bound P as a function of collection method. In-channel sources were the largest proportional SS source, regardless of season, hydrologic condition, collection method, or source scenario. Source verification highlighted which source fingerprints were most accurately defined and implications for SS target apportionment. Conclusion Varying the source scenarios for sediment fingerprinting indicated that improved management of hydrologic connectivity between upland land use and the stream channel has the potential to mitigate SS loads.

Finite element modeling of the glass sealing process for solid oxide cell stacks - James Fitzpatrick; Kerry Meinhardt; Naveen Karri; Brian Koeppel; Jie Bao; Tongan Jin; Lorraine Seymour; Nathan Royer; Olga A. Marina (Chemical Engineering Journal, 2024)

Sediment budget of a Maumee River headwater tributary: how streambank erosion, streambed-sediment storage, and streambed-sediment source inform our understanding of legacy phosphorus - Tanja N. Williamson; Faith A. Fitzpatrick; Rebecca M. Kreiling; James D. Blount; Diana L. Karwan (Journal of Soils and Sediments, 2024)
Objective We described source and phosphorus (P) retention potential of soft, fine-grained, streambed sediment and associated phosphorus (sed-P) during summer low-flow conditions. Combining in-channel, sed-P storage with relative age provided context on relevance to western Lake Erie Basin management goals. Methods In 2019, rapid geomorphic assessment (30 reaches) compared streambed-sediment storage (S) to streambank erosion (E), providing annual sediment budgets (S:E). Streambed sediment (13 reaches) was fingerprinted and analyzed for sed-P. The P saturation ratio (PSR; four reaches) quantified potential sorption/desorption of dissolved P (DP) between the water column and streambed sediment. Analyses were supplemented with data from 2017 and 2021. The ratio of two fallout radionuclides, beryllium-7 (54-day half-life) and excess lead-210 (22.3 years), apportioned “new” sediment based on time since rainfall contact. Results Streambed sediment was mostly streambank (54–96%) for contributing areas > 2.7 km 2 ; for upstream reaches, a larger percentage was apportioned as upland (cropland, pasture, forest, and road), with < 30% streambank. Streambank erosion correlated with contributing area; however, soil type (ecoregion), stream characteristics, and land use combined to drive streambed-sediment storage. Individual-reach S:E (accumulation of 0.01–35 years of streambank erosion) differentiated erosional and depositional in-channel environments. Most reaches indicated that 17–57% of sediment had recent contact with rainfall. Streambed-sediment PSR indicated a low potential for further sorption of DP from the water column; one reach was a P source when sampled. Conclusion Sed-P was higher in streambed sediment than in source samples, which varied by land use and ecoregion. This indicates homogenization resulting from in-stream sorption of DP during sediment transport that occurs over multiple events.

Product repair in a circular economy: Exploring public repair behavior from a systems perspective - Keshav Parajuly; James Green; Jessika Richter; Michael Johnson; Jana Rückschloss; Jef Peeters; Ruediger Kuehr; Colin Fitzpatrick (Journal of Industrial Ecology, 2024)
Repair practices are driven not only by consumers’ internal motivation, but also by external infrastructural, social including cultural, financial, and political factors. We explore these factors with the goal of understanding the public repair of electrical and electronic products (e‐products) from a systems perspective to help devise appropriate change interventions. We document (a) behavioral aspects, (b) techno‐economic factors, and (c) intervention strategies aimed at promoting repair practices. To gauge this, a survey was administered among 922 volunteers across 14 countries with experience in repairing e‐products at public repair events. Findings suggest that while behavioral constructs including personal values, beliefs, and attitudes toward product repair are the main proximal drivers of intention to repair, the ability to repair plays an important role. Further, these individual factors are influenced by the techno‐economic settings such as access to repair services, economic benefits, and the ease of product repair stands out as the key enablers for product lifetime extension. As per intervention strategies, the results highlight economic incentives, regulatory requirements, and public awareness as the key drivers. However, influencing repair behavior directly may not always be the most effective strategy. New initiatives to improve involvement should focus on more repairable products, exploiting the innovative potentials of commercial as well as non‐profit repair initiatives, education, and supporting the development of skills among volunteer repairers.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Correction to: Size-Dependent Effective Diffusivity in Healthy Human and Porcine Joint Synovium - Young Guang; Alexandra L. Davis; Thomas M. McGrath; Christine T. N. Pham; James A. J. Fitzpatrick; Lori A. Setton (Annals of Biomedical Engineering, 2022)

Pharmacological inhibition of MERTK induces in vivo retinal degeneration: a multimodal imaging ocular safety assessment - Gregory Hamm; Gareth Maglennon; Beth Williamson; Ruth Macdonald; Ann Doherty; Stewart Jones; Jayne Harris; James Blades; Alexander R. Harmer; Peter Barton; Philip B. Rawlins; Paul Smith; et al. (Archives of Toxicology, 2022)
The receptor tyrosine kinase, MERTK, plays an essential role in homeostasis of the retina via efferocytosis of shed outer nuclear segments of photoreceptors. The Royal College of Surgeons rat model of retinal degeneration has been linked to loss-of-function of MERTK, and together with the MERTK knock-out mouse, phenocopy retinitis pigmentosa in humans with MERTK mutations. Given recent efforts and interest in MERTK as a potential immuno-oncology target, development of a strategy to assess ocular safety at an early pre-clinical stage is critical. We have applied a state-of-the-art, multi-modal imaging platform to assess the in vivo effects of pharmacological inhibition of MERTK in mice. This involved the application of mass spectrometry imaging (MSI) to characterize the ocular spatial distribution of our highly selective MERTK inhibitor; AZ14145845, together with histopathology and transmission electron microscopy to characterize pathological and ultra-structural change in response to MERTK inhibition. In addition, we assessed the utility of a human retinal in vitro cell model to identify perturbation of phagocytosis post MERTK inhibition. We identified high localized total compound concentrations in the retinal pigment epithelium (RPE) and retinal lesions following 28 days of treatment with AZ14145845. These lesions were present in 4 of 8 treated animals, and were characterized by a thinning of the outer nuclear layer, loss of photoreceptors (PR) and accumulation of photoreceptor outer segments at the interface of the RPE and PRs. Furthermore, the lesions were very similar to that shown in the RCS rat and MERTK knock-out mouse, suggesting a MERTK-induced mechanism of PR cell death. This was further supported by the observation of reduced phagocytosis in the human retinal cell model following treatment with AZ14145845. Our study provides a viable, translational strategy to investigate the pre-clinical toxicity of MERTK inhibitors but is equally transferrable to novel chemotypes.

Evaluation of Norovirus Reduction in Environmentally Contaminated Pacific Oysters During Laboratory Controlled and Commercial Depuration - Agnieszka Rupnik; William Doré; Leon Devilly; James Fahy; Amy Fitzpatrick; Wiebke Schmidt; Kevin Hunt; Francis Butler; Sinéad Keaveney (Food and Environmental Virology, 2021)
Norovirus contamination of oysters is the lead cause of non-bacterial gastroenteritis and a significant food safety concern for the oyster industry. Here, norovirus reduction from Pacific oysters ( Crassostrea gigas), contaminated in the marine environment, was studied in laboratory depuration trials and in two commercial settings. Norovirus concentrations were measured in oyster digestive tissue before, during and post-depuration using the ISO 15216-1 quantitative real-time RT-PCR method. Results of the laboratory-based studies demonstrate that statistically significant reductions of up to 74% of the initial norovirus GII concentration was achieved after 3 days at 17–21 °C and after 4 days at 11–15 °C, compared to 44% reduction at 7–9 °C. In many trials norovirus GII concentrations were reduced to levels below 100 genome copies per gram (gcg −1 ; limit of quantitation; LOQ). Virus reduction was also assessed in commercial depuration systems, routinely used by two Irish oyster producers. Up to 68% reduction was recorded for norovirus GI and up to 90% for norovirus GII reducing the geometric mean virus concentration close to or below the LOQ. In both commercial settings there was a significant difference between the levels of reduction of norovirus GI compared to GII ( p < 0.05). Additionally, the ability to reduce the norovirus concentration in oysters to < LOQ differed when contaminated with concentrations below and above 1000 gcg −1 . These results indicate that depuration, carried out at elevated (> 11 °C) water temperatures for at least 3 days, can reduce the concentration of norovirus in oysters and therefore consumer exposure providing a practical risk management tool for the shellfish industry.

Size-Dependent Effective Diffusivity in Healthy Human and Porcine Joint Synovium - Young Guang; Alexandra L. Davis; Thomas M. McGrath; Christine T. N. Pham; James A. J. Fitzpatrick; Lori A. Setton (Annals of Biomedical Engineering, 2021)

Functioning of Coastal River-Dominated Ecosystems and Implications for Oil Spill Response: From Observations to Mechanisms and Models - Adam Greer; Alan Shiller; Eileen Hofmann; Jerry Wiggert; Sally Warner; Sabrina Parra; Chudong Pan; Jeffrey Book; DongJoo Joung; Steven Dykstra; Jeffrey Krause; Brian Dzwonkowski; et al. (Oceanography, 2018)

Residence Time of a Highly Urbanized Estuary: Jamaica Bay, New York - Reza Marsooli; Philip M. Orton; James Fitzpatrick; Heather Smith (Journal of Marine Science and Engineering, 2018)
Using a validated coupled hydrodynamic-tracer transport model, this study quantified the mean residence time in Jamaica Bay, a highly eutrophic lagoonal estuary in New York City. The Bay is a well-mixed to partially-stratified estuary with heavily-dredged bathymetry and substantial wastewater treatment plant effluent inputs that lead to seasonal hypoxia in some poorly-flushed deep-water basins. Residence time was computed for Jamaica Bay and its largest isolated deep basin, Grassy Bay. The response of residence time to freshwater discharge and wind forcing during summer 2015 was also investigated. The model results showed that the mean residence time, which represents the time required to flush out 63% of tracers released into the region of interest, was 17.9 days in Jamaica Bay and 10.7 days in Grassy Bay. The results also showed that some regions in Jamaica Bay retained their tracers much longer than the calculated residence time and, thus, are potentially prone to water quality problems. Model experiments demonstrated that summertime wind forcing caused a small increase in residence time, whereas freshwater discharge substantially reduced residence time. Freshwater inputs were shown to strongly enhance the two-layer estuarine gravitational circulation and vertical shear, which likely reduced residence time by enhancing shear dispersion. Due to the Bay’s small, highly-urbanized watershed, freshwater inputs are largely derived from the municipal water supply, which is fairly uniform year-round. This water helps to promote bay flushing, yet also carries a high nitrogen load from wastewater treatment. Lastly, the tidal prism method was used to create a simple calibrated model of residence time using the geometry of the study area and the tidal range and period.

A hierarchical Bayesian model to incorporate uncertainty into methods for diversity partitioning - Zachary H. Marion; James A. Fordyce; Benjamin M. Fitzpatrick (Ecology, 2018)
Recently there have been major theoretical advances in the quantification and partitioning of diversity within and among communities, regions, and ecosystems. However, applying those advances to real data remains a challenge. Ecologists often end up describing their samples rather than estimating the diversity components of an underlying study system, and existing approaches do not easily provide statistical frameworks for testing ecological questions. Here we offer one avenue to do all of the above using a hierarchical Bayesian approach. We estimate posterior distributions of the underlying “true” relative abundances of each species within each unit sampled. These posterior estimates of relative abundance can then be used with existing formulae to estimate and partition diversity. The result is a posterior distribution of diversity metrics describing our knowledge (or beliefs) about the study system. This approach intuitively leads to statistical inferences addressing biologically motivated hypotheses via Bayesian model comparison. Using simulations, we demonstrate that our approach does as well or better at approximating the “true” diversity of a community relative to naïve or ad‐hoc bias‐corrected estimates. Moreover, model comparison correctly distinguishes between alternative hypotheses about the distribution of diversity within and among samples. Finally, we use an empirical ecological dataset to illustrate how the approach can be used to address questions about the makeup and diversities of assemblages at local and regional scales.

Pairwise beta diversity resolves an underappreciated source of confusion in calculating species turnover - Zachary H. Marion; James A. Fordyce; Benjamin M. Fitzpatrick (Ecology, 2017)
Beta diversity is an important metric in ecology quantifying differentiation or disparity in composition among communities, ecosystems, or phenotypes. To compare systems with different sizes ( N , number of units within a system), beta diversity is often converted to related indices such as turnover or local/regional differentiation. Here we use simulations to demonstrate that these naive measures of dissimilarity depend on sample size and design. We show that when N is the number of sampled units (e.g., quadrats) rather than the “true” number of communities in the system (if such exists), these differentiation measures are biased estimators. We propose using average pairwise dissimilarity as an intuitive solution. That is, instead of attempting to estimate an N ‐community measure, we advocate estimating the expected dissimilarity between any random pair of communities (or sampling units)—especially when the “true” N is unknown or undefined. Fortunately, measures of pairwise dissimilarity or overlap have been used in ecology for decades, and their properties are well known. Using the same simulations, we show that average pairwise metrics give consistent and unbiased estimates regardless of the number of survey units sampled. We advocate pairwise dissimilarity as a general standardization to ensure commensurability of different study systems.

Can genetic data confirm or refute historical records? The island invasion of the small Indian mongoose (Herpestes auropunctatus) - Arijana Barun; Matthew L. Niemiller; Benjamin M. Fitzpatrick; James A. Fordyce; Daniel Simberloff (Biological Invasions, 2013)

Characterization of 18 polymorphic microsatellite loci from invasive lionfish (Pterois volitans and P. miles) - Thomas F. Schultz; Cristin Keelin Fitzpatrick; D. Wilson Freshwater; James A. Morris (Conservation Genetics Resources, 2013)

Doomed before they are described? The need for conservation assessments of cryptic species complexes using an amblyopsid cavefish (Amblyopsidae: Typhlichthys) as a case study - Matthew L. Niemiller; Gary O. Graening; Dante B. Fenolio; James C. Godwin; James R. Cooley; William D. Pearson; Benjamin M. Fitzpatrick; Thomas J. Near (Biodiversity and Conservation, 2013)

What can DNA tell us about biological invasions? - Benjamin M. Fitzpatrick; James A. Fordyce; Matthew L. Niemiller; R. Graham Reynolds (Biological Invasions, 2012)

The Molecular Phylogeny of a Nematode-Specific Clade of Heterotrimeric G-Protein α-Subunit Genes - Damien M. O’Halloran; David A. Fitzpatrick; Grace P. McCormack; James O. McInerney; Ann M. Burnell (Journal of Molecular Evolution, 2006)

Evidence of Positive Darwinian Selection in Putative Meningococcal Vaccine Antigens - David A. Fitzpatrick; Christopher J. Creevey; James O. McInerney (Journal of Molecular Evolution, 2005)

Evidence of Positive Darwinian Selection in Omp85, a Highly ConservedBacterial Outer Membrane Protein Essential for Cell Viability - David A. Fitzpatrick; James O. McInerney (Journal of Molecular Evolution, 2005)

Multi-locus DNA fingerprinting supports genetic monogamy in Florida scrub-jays - James S. Quinn; Glen E. Woolfenden; John W. Fitzpatrick; Bradley N. White (Behavioral Ecology and Sociobiology, 1999)